2019
DOI: 10.1002/pro6.1068
|View full text |Cite
|
Sign up to set email alerts
|

Carboxypeptidase A4 promotes migration and invasion of lung cancer cells, and is closely associated with lymph node metastasis

Abstract: Objective The incidence and mortality rate of lung cancer ranks first among all malignant tumors. Lymph node metastasis is the most common mode of metastasis in lung cancer, and it is also an important indicator for treatment strategies and prognosis. Several studies have shown that the carboxypeptidase family plays important roles in cancer metastasis. In the present study, we investigated the effect of carboxypeptidase A4 (CPA4) on human lung cancer cells, and the clinical significance of its levels in lung … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Previous studies reported expression of CPA4 expression in 72.7% and 57.5 % of lung adenocarcinoma cases which is similar to our results in proving the diagnostic role of such biomarker in lung adenocarcinoma. The variety in number of positive cases between our results and their results was due to differences in number of included cases or type of used antibodies in our studies and their studies [18,19].…”
Section: Prognostic Values Of Cpa4 Uhrf1 Cd90 and Glypican-1expressio...mentioning
confidence: 50%
“…Previous studies reported expression of CPA4 expression in 72.7% and 57.5 % of lung adenocarcinoma cases which is similar to our results in proving the diagnostic role of such biomarker in lung adenocarcinoma. The variety in number of positive cases between our results and their results was due to differences in number of included cases or type of used antibodies in our studies and their studies [18,19].…”
Section: Prognostic Values Of Cpa4 Uhrf1 Cd90 and Glypican-1expressio...mentioning
confidence: 50%